Steady-flow experiments in urban areas and anisotropic porosity model. Issue 1 (2nd January 2017) - Velickovic, Mirjana; Zech, Yves; Soares-Frazão, Sandra
ABSTRACT: Modelling flow through an urban area is challenging because of the significant difference between the scale of individual streets and the whole district scale. This paper presents idealized experiments where buildings are represented by square blocks. The experiments were designed to highlight the effect of the street width and orientation to the main flow direction. In addition, a porosity model is developed for representing the urban district as a whole without considering the detailed geometry of the streets, but accounting for the main effects on the flow. The model introduces a tensor of drag coefficients aimed at representing directional effects. The drag coefficients are calibrated and validated using the experimental results.